2016
DOI: 10.1016/j.bpj.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Inhibitors Have Distinct Effects, but Also Common Modes of Action, in the HCV Polymerase

Abstract: Recently discovered information alters the interpretation of our paper published previously in Biophysical Journal. In the study, we used molecular dynamics (MD) simulations to understand the mechanisms that govern allosteric inhibition of the RNA polymerase from hepatitis C virus (HCV). Our findings revealed that allosteric inhibitors alter the conformations adopted by the enzyme in a manner that allows their inhibitory effects to be readily understood. Their primary modes of action were found to be: 1) restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…These conformations are mainly characterized by the extent of opening of the polymerase, following rotation of the thumb subdomain with respect to palm and fingers. For example, 1) a crystal structure of NS5B has revealed the presence of two conformations (30), one being more open than the other; 2) NS5B has been shown to be able to bind a circular RNA template (92), which implies opening of its encircled closed active site; and 3) molecular simulations have suggested that NS5B may sample a conformational space in which the intersubdomain angle and the RNA channel width can vary significantly (36). Recently, Deredge et al have shown using hydrogen/deuterium exchange followed by MS that fingers, palm, and, to a lesser extent, the core of the thumb are highly exchange-protected regions of apo-NS5B (42).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These conformations are mainly characterized by the extent of opening of the polymerase, following rotation of the thumb subdomain with respect to palm and fingers. For example, 1) a crystal structure of NS5B has revealed the presence of two conformations (30), one being more open than the other; 2) NS5B has been shown to be able to bind a circular RNA template (92), which implies opening of its encircled closed active site; and 3) molecular simulations have suggested that NS5B may sample a conformational space in which the intersubdomain angle and the RNA channel width can vary significantly (36). Recently, Deredge et al have shown using hydrogen/deuterium exchange followed by MS that fingers, palm, and, to a lesser extent, the core of the thumb are highly exchange-protected regions of apo-NS5B (42).…”
Section: Discussionmentioning
confidence: 99%
“…7f; see supplemental Fig. S7), which has been shown to reduce functional dynamics in NS5B (36,41,42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations